2014
DOI: 10.1109/tdei.2013.004145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticle surface modification on charge transport characteristics in XLPE/SiO2 nanocomposites

Abstract: This paper focuses on the effect of nanoparticle surface modification on the charge transport characteristics in XLPE/SiO 2 nanocomposites. A titanate coupling agent (TC9) and a 3-(Methacryloyloxy)propyltrimethoxysilane (KH570) were used for the surface modification of SiO 2 nanoparticles. It was found that both KH570 and TC9 coupling agents improve the nanoparticle dispersion compared with unmodified SiO 2 nanoparticles. The improvement in dispersion was found to be due to increased surface hydrophobicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Since T. J. Lewis [11] first proposed the concept of nanodielectrics in 1994, polyethylene-based nanocomposites have developed from LDPE nanocomposites to XLPE nanocomposites. It has been demonstrated that XLPE nanocomposites can improve electrical properties [12][13][14][15][16][17]. The interface in nanocomposites between the polymer matrix and nanoparticles is the main reason for the improvement in the electrical properties [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Since T. J. Lewis [11] first proposed the concept of nanodielectrics in 1994, polyethylene-based nanocomposites have developed from LDPE nanocomposites to XLPE nanocomposites. It has been demonstrated that XLPE nanocomposites can improve electrical properties [12][13][14][15][16][17]. The interface in nanocomposites between the polymer matrix and nanoparticles is the main reason for the improvement in the electrical properties [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, most studies have been limited to the insulation nano-doped polyethylene, which has been attracting more and more attention. It has been reported that polyethylene-doped inorganic nanoparticles such as MgO, ZnO and SiO 2 can significantly suppress the accumulation of space charge in the insulation [21][22][23][24][25]. Some researchers add SrFe 16 O 19 to the semiconductive layer to reduce the injection of space charge in the insulating layer by using the Lorentz force of magnetic particles on the charge [26].…”
Section: Ball Milling Of Lscmentioning
confidence: 99%
“…Meanwhile, charges would be injected from the electrode into the material. The charges originating from above sources can be trapped and then space charge accumulation takes place [23]. Since the positive ion is heavier than the electron, the mobility of the positive ion is much lower than that of the electron with the same electricity under the same applied electric field.…”
Section: Space Charge Distributionmentioning
confidence: 99%